(untitled) (The Planet, 2021)
Introduction: The population of a country or a defined area is largely determined by three variables-deaths (mortality), births (fertility) and migration. The balance between these variables determine whether a population decreases or increases in number. The rapid population growth could be controlled by reducing the birth through increasing the use of contraceptives along with other measures. Objectives: The objective of the study was to find out the prevalence of contraceptive use among married women of reproductive age group (15 -49 years). Materials and Methods: This was a descriptive type of crosssectional study which was carried out among 200 Rural Reproductive age group (15-49 years) married women. The study was conducted in a selected Rural Area in Gazipur district. Pretested semi-structured questionnaire was used for data collection after taking informed written consent from the Respondents which included information regards to socio-demographic status, types and related other information’s of contraceptive methods used by the respondents. Results: The study revealed that maximum age of the respondent were between 21-30 years (45%), 31-40 years age group was 35% and in both 15-20 years and 41-49 years age groups were 10%. Majority of[144(72%)]respondents were from nuclearfamily, and 130(65%) respondents had 3-5 family members. Most of the respondents 180(90%) were homemaker. Husbands of most 105(52.5%) of the respondents were businessman. Family income of maximum 116 (58%) respondents was within the range of 10,000/-20,000/ Tk. Among all the respondents, 151(75.5%) were using contraceptive methods. Among the users of contraceptive methods majority 74(37%) had been using oral contraceptive pills, followed by injectable contraceptive user [37(18.5%)], barrier method [32(16%)] then permanent method and IUCD user. None were implant-users. About 27% (54) respondents were using contraceptive method for more than 5 years, 21% (42) were using contraceptive method for 3-5 years duration, 20%(40) were using for the duration of 1-2 years. Rest 15(7.5%) were using contraceptive method for less than one year. Conclusion: In this study we found that contraceptive prevalence rate (75.5%) is little higher than our national contraceptive prevalence rate (62.5%) but about 25% were not using any contraceptive methods due to different reasons. In order to improve contraceptive use we need to extend provision of health education to educate couples, their parents, family members and society.